ECOLOGICAL STUDY OF THE ARROWROOT (Tacca leontopetaloides (L.) Kuntze) AT KARIMUNJAWA NATIONAL PARK, CENTRAL JAVA - Laode Alhamd (Research Center for Biology, 2018)
ALHAMD, L. 2018. Ecological study of the arrowroot (Tacca leontopetaloides (L.) Kuntze) at Karimunjawa National Park, Central Java. Reinwardtia 17(2): 87–96. — An ecological study of arrowroot (Tacca leontopetaloides (L.) Kuntze) at Karimunjawa National Park (Karimunjawa NP), Central Java, was conducted at six islands, namely Kumbang, Nyamuk, Katang, Seruni, Cendikia and Sintok islands. A sampling plot of 10 × 50 m2 was established on each island. The results showed that the arrowroot population in Katang island was greater than those of other islands, with a density of 0.74 m-2, a frequency of 0.8 and an abundance of 23.1. The arrowroot density of all samplings ranged from 137 to 370 per 0.05 ha. The occurrence of 30 species surrounding arrowroot was observed and only five species, Sida acuta (Chi-square count (cs)>Chi-square table cs=5.71, P<0.05) and Scaevola taccada (cs=7.94, P<0.01) in Kumbang island, Imperata cylindrica (cs=18.81, P<0.01) in Nyamuk island, Morinda citrifolia (cs=9.47, P<0.01) in Sintok island, and Carica papaya (cs=3.95, P<0.05) in Cendikia island, had significant associations with arrowroot. For habitat characteristics, soil textures were dominated by sandy types ranging from 90 to 95%, whilst other soil properties such as pH, N, P, K, Mg and CEC did not significantly affect the presence of arrowroot.